Physicochemical properties of Bruguiera gymnorrhiza flour (BGF) - Amin, M. N. G, ,- (University Putra Malaysia, 2018)
This research aims to study the physicochemical properties of Bruguiera gymnorrhiza flour (BGF). The peeled BG fruit was immersed in ash suspension in water (10% w/v) for 24 hours, then sundried, milled, and sieved through membrane sized 100 mesh. Particle size of BGF produced as described are of 150 µm, brown in colour, of low viscosity and adhesiveness (CR:30.25), low amylose content (14.23%), had low protein (4.82%) and fat (0.24%) content, and high crude fiber content (7.46%). Tanin content of BG fruit was succesfully reduced by pretreatment in this study (19700 ppm to 8500 ppm). HCN content in BG fruit were under the detection limits of our method to be determined. Results of the present study suggests futher studies on the use of BGF for developing flat bread ingredients.